DRUG DISTRIBUTION AND CHEMICAL PROCESSES OF MEDICINES: AN OUTLOOK - Jain, Kumar Gaurav (ShodhKosh: Journal of Visual and Performing Arts, 2022)
The classification and grouping of drugs can often be a source of confusion, primarily because different textbooks and reference materials employ various methods of categorization. These methods are based on different criteria, such as pharmacological properties, therapeutic uses, or chemical structure, leading to multiple and sometimes conflicting classification systems. As a result, navigating through the vast array of drug classifications can be challenging, requiring careful attention to the specific approach each source uses. This variability in drug categorization often makes it more difficult for students, professionals, and researchers to develop a clear and consistent understanding of how drugs are grouped and categorized within the field. While attempting to understand the basics of drug classification, we shall briefly delve into the intricacies and processes of medicinal chemistry as well, in this paper.